Improving critical thinking and problem-solving skills through POGIL combined with digital mind map - Mafazatud Diniyyah; Herawati Susilo; B. Balqis; Ahmad Kamal Sudrajat (University of Muhammadiyah Malang, 2022)
Critical thinking and problem-solving skills are necessary skills in the 21st century learning. However, the initial tests of students' critical thinking and problem-solving skills showed low scores. Therefore, the purpose of this study was to improve students’ critical thinking and problem-solving skills through the POGIL (Process Oriented Guided Inquiry Learning) model combined with a digital mind map based on online learning. This study uses the Classroom Action Research (CAR) method following the design of Kemmis & McTaggart, which consists of 4 stages, namely planning, implementing the action, observing, and reflecting. The stages of the POGIL model consist of orientation, exploration, concept formation combined with making digital mind maps, applications, and closings. The research subjects were students of class XI MIPA 4 of SMAN 2 Malang, totalling 28 students which consisted of twenty girls and eight boys. The percentage of critical thinking skills achievement increased by 29.61% from 66.87% in the first cycle to 86.67% in the second cycle. Problem-solving skills increased by 22.16% from 70.27% in the first cycle to 85.84% in the second cycle. The results showed that the POGIL model combined with a digital mind map based on online learning could improve students’ critical thinking and problem-solving skills.